An assessement of the effectiveness of public participation programmes on service delivery in the Capricorn District Municipality, Limpopo Province - Mosotho, Malebese Alexander (My University, 2013)
The study has focused on the evaluation of effectiveness of public participation programmes towards service delivery within the Capricorn District Municipality. Public participation is supported by various pieces of legislation, such as the Constitution (1996) and the Municipal Systems Act (2000), which has placed the community at the centre of development in the local government sphere. It also occupies a key position for development within local government, as it is important in assessing successes and failures of programmes. In this study, the researcher used interview schedules as an instrument to assess the effectiveness of public participation programmes towards service delivery within the Capricorn District Municipality. The researcher used this instrument to get the views of the respondents - in this case ward committees - about effectiveness of public participation programmes in the Aganang and Blouberg Local Municipalities as the area of the study. The findings of the research revealed that there is lack of effective participation in municipal programmes by the community due to a lack of confidence in the local authority, in terms of providing regular feedback on commitments made about service delivery. The findings also revealed that a lack of education plays a significant role for the effective participation of communities within the municipal programmes. Based on the findings of the research, recommendations were made that mechanisms should be implemented to monitor the impact of public participation programmes, building community capacity to engage with municipalities as well as strengthening current public participation mechanisms (such as the IDP consultation process, public hearings and outreach programmes).
Thesis (MPA.) -- University of Limpopo, 2013
Keywords: Public participation; Service delivery; Public administration -- Citizen participation; Municipal services -- South Africa; Local government -- South Africa; Community development -- South Africa